Functional modulation of cytochrome C upon specific binding to DNA nanoribbons. Issue 93 (7th November 2019) - Ouyang, Xiangyuan; Wang, Si-Yao; Liu, Ting; Ren, Yong-An; Wang, Mei-Fang; Chen, Fang-Fang; Wang, Li-Li
Abstract : We discovered that the redox activity of cytochrome C can be enhanced and its peroxidase activity can be decreased by DNA nanoribbons. Abstract : We discovered that the function of cytochrome C can be modulated by DNA nanoribbons. Meanwhile, the interplay between the DNA nanoribbons and the native cytochrome C and the possible mechanisms are also discussed.